Learning The Vocabulary of Arabic Language: Sociolinguistic Approach - Baiq Wahyu Diniyati; Syauqa Tsaqila; Abul Maali (Kitaba, 2023)
Education experts continue to improve the learning of the Arabic language in Indonesia to obtain an optimal method and a good approach. This research aims to provide a clear understanding of learning Arabic vocabulary with the sociolinguistic approach and how to learn Arabic vocabulary with the sociolinguistic approach, as well as the contribution of the sociolinguistic approach to learning Arabic vocabulary. This study is considered very important because the research did not find a sociolinguistic approach to learning Arabic vocabulary in particular. The research used was qualitative research from desk research. The sociolinguistic approach to learning Arabic vocabulary provides a broader understanding of language usage in social contexts. By learning Arabic vocabulary in social and cultural contexts students can develop more realistic communication skills and understand the nuances of language used in everyday situations. This research has many limitations, so the researcher hoped to continue with more in-depth research on the sociolinguistic approach to vocabulary learning.